Insurance is a Strong Financial Instrument in the Socio-Economic Development of the Country - Khalikulova Gulzada Tadjimuratovna (Research Parks Publishers, 2023)
In this article, the foreign experience of insurance activities, issues of implementation procedure are considered. The directions of development of the insurance market of Uzbekistan are analyzed. Proposals and recommendations were also demonstrated to help the development of the insurance market.